ANALISIS PENGARUH KUALITAS WEBSITE E-LEARNING UJIAN ONLINE SMK PELAYARAN AMPARI JAYAPURA - Natalia Betty Ansanay; Emy L. Tatuhey (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to evaluate end-user satisfaction with the online exam e-learning website at SMK Pelayaran Ampari Jayapura using the End User Computing Satisfaction (EUCS) method. The EUCS framework consists of five key variables: content, accuracy, format, ease of use, and timeliness. Data was collected through questionnaires distributed to 60 active students who had used the website for online examinations. The data analysis results show that the average scores for each variable are as follows: content 3.97; accuracy 3.88; format 3.85; ease of use 3.90; and timeliness 3.83. Among these variables, content received the highest score, indicating that the information presented on the system is perceived as relevant and useful by the users. On the other hand, timeliness obtained the lowest score, highlighting a need for improvement in the system’s responsiveness and punctuality in delivering information or access to exams. The overall average score of 3.89 suggests that users are generally satisfied with the system. Based on these findings, it is recommended that improvements focus on enhancing system performance, particularly in terms of access speed, exam scheduling, and user interface features to make the platform more interactive and responsive. The results of this study are expected to serve as strategic input for system developers and administrators in improving the quality of e-learning services, especially for the effective and efficient implementation of online assessments in vocational high school settings.